Janusarene: A Homoditopic Molecular Host. (13th July 2017) - Li, Tao; Fan, Luoyi; Gong, Hao; Xia, Zeming; Zhu, Yanpeng; Jiang, Nianqiang; Jiang, Long; Liu, Gaofeng; Li, Yang; Wang, Jiaobing
Abstract: A homoditopic molecular host, janusarene, is presented that has two back‐to‐back compactly arranged nanocavities for guest complexation. The unique two‐face structural feature of janusarene allows it to bind and align various guest compounds concurrently, which include spherical pristine fullerene C60 and planar polycyclic aromatic hydrocarbons (PAHs), such as pyrene, perylene, and 9, 10‐dimethylanthracene. The host–guest interactions were characterized by single‐crystal X‐ray diffraction. A pairwise encapsulation of the PAH guests by janusarene enables PAH dimers to be obtained that deliver spectroscopic properties distinct from those of PAHs dissolved in solution, or in the bulk state. A monotopic control host was also synthesized and used to characterize the host–guest complexing behavior in solution.